The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14148323
|View full text |Cite
|
Sign up to set email alerts
|

Compound Positioning Method for Connected Electric Vehicles Based on Multi-Source Data Fusion

Abstract: With the development of electrified transportation, electric vehicle positioning technology plays an important role in improving comprehensive urban management ability. However, the traditional positioning methods based on the global positioning system (GPS) or roadside single sensors make it hard to meet requirements of high-precision positioning. Considering the advantages of various sensors in the cooperative vehicle-infrastructure system (CVIS), this paper proposes a compound positioning method for connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In [45] the authors present the benefits of the cooperation of different sensors in the so-called Cooperative Vehicle-Infrastructure System (CVIS) in the context of Connected Electric Vehicles (CEVs). The approach is based on the merging of different data coming from different devices in supporting the cooperative system.…”
Section: Cooperative Positioning Techniquesmentioning
confidence: 99%
“…In [45] the authors present the benefits of the cooperation of different sensors in the so-called Cooperative Vehicle-Infrastructure System (CVIS) in the context of Connected Electric Vehicles (CEVs). The approach is based on the merging of different data coming from different devices in supporting the cooperative system.…”
Section: Cooperative Positioning Techniquesmentioning
confidence: 99%
“…Data augmentation is a helpful approach for designing an ML model since it allows researchers to increase the size of the learning data without having to acquire new data [125]. Fusion of multi-source dataset, including historical velocity data, video, or image information, also can significantly enhance the training and performance of ML models in optimizing energy consumption [179]. By combining different data sources, the model can capture a more comprehensive understanding of the underlying patterns and relationships within the energy system.…”
Section: Preprocessing Tasksmentioning
confidence: 99%
“…Multi-source sensor information fusion for mechanical fault diagnosis is still in its infancy due to its complexity and feature extraction and fusion issues [24,25]. Due to the rapid development of deep learning-related research results, designing a complete fault diagnosis system based on multi-source information fusion using deep learning to realize the algorithm structure, including data preprocessing, classifiers, and evidence fusion, has become important [26,27]. Ghosh et al [28] discovered an evidence theory and multiinformation fusion to effectively-identified composite faults and provided maintenance instructions for composite fault diagnosis by fussing several maximal statistical distances and identifying fault classes technique.…”
Section: Introductionmentioning
confidence: 99%